2012
DOI: 10.1074/jbc.m112.379230
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of sahH Reveals That Biofilm Formation Is Autoinducer-2-independent in Streptococcus sanguinis but Is Associated with an Intact Activated Methionine Cycle

Abstract: Background: AI-2 is a by-product of the LuxS-mediated reaction within the activated methionine cycle (AMC). Results:The biofilm phenotype of a S. sanguinis luxS mutant was restored by SahH expression but not by AI-2 supplementation. Conclusion:The luxS mutant biofilm phenotype is not caused by lacking AI-2 but by an AMC defect. Significance: The SahH bypass is essential for further studies on AI-2 utilizing luxS mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 70 publications
2
17
0
Order By: Relevance
“…AI-2 independent effects of LuxS have also been reported in other organisms. For example, LuxS-dependent biofilm formation by Streptococcus sanguinis does not require DPD pools but is associated with an intact activated methionine cycle [30]. Transcriptome analysis of the P. gingivalis luxS mutant indicated that luxS is involved in both AI-2 dependent, and AI-2 independent gene regulation [23].…”
Section: Discussionmentioning
confidence: 98%
“…AI-2 independent effects of LuxS have also been reported in other organisms. For example, LuxS-dependent biofilm formation by Streptococcus sanguinis does not require DPD pools but is associated with an intact activated methionine cycle [30]. Transcriptome analysis of the P. gingivalis luxS mutant indicated that luxS is involved in both AI-2 dependent, and AI-2 independent gene regulation [23].…”
Section: Discussionmentioning
confidence: 98%
“…Hence, the luxS gene expression is apparently not depending on (or correlating with) AI-2 levels (Siller et al 2008;Han and Lu 2009;Vidal et al 2011). When this strain was complemented with an alternative route of the AMC, preventing the accumulation of S-adenosylhomocystein, only nine genes showed altered transcription in comparison to the wild type (Redanz et al 2012). Anyway, phenotypes caused by the deletion of luxS might not necessarily be associated with the lack of AI-2 production but could be caused by the accumulation of toxic intermediates of the AMC such as S-adenosylhomocystein, as recently described for Streptococcus sanguinis (Redanz et al 2012).…”
Section: Luxs and Ai-2 Dependent Quorum Sensingmentioning
confidence: 57%
“…In batch cultures, the highest luxS expression level can be observed during early exponential growth while maximum AI-2 secretion is reached in the transition phase. Anyway, phenotypes caused by the deletion of luxS might not necessarily be associated with the lack of AI-2 production but could be caused by the accumulation of toxic intermediates of the AMC such as S-adenosylhomocystein, as recently described for Streptococcus sanguinis (Redanz et al 2012). Although it has been shown that luxS transcription is induced by iron in S. pneumoniae or repressed by the CovR (CsrR) response regulator in S. pyogenes, the regulatory mechanisms controlling luxS expression and AI-2 production in streptococci are not well understood Trappetti et al 2011).…”
Section: Luxs and Ai-2 Dependent Quorum Sensingmentioning
confidence: 94%
“…mutans , S . sanguinis biofilm formation was independent of AI-2 quorum sensing [51], and vicRK exhibited a negative regulation of gtfP transcription at certain growth stages [52], making the regulation S . sanguinis gtfP more complicated.…”
Section: Discussionmentioning
confidence: 99%